Crossing of the Cystic Barriers of Toxoplasma gondii by the Fluorescent Coumarin Tetra-Cyclopeptide - Céline Dard; Baptiste Leforestier; Flaviane Francisco Hilário; Mohamed Dit Mady Traoré; Marie-Ange Lespinasse; Basile Pérès; Marie-Carmen Molina; Rossimiriam Pereira de Freitas; Anne Milet; Danièle Maubon; Yung-Sing Wong (Molecules, 2021)
FR235222 is a natural tetra-cyclopeptide with a strong inhibition effect on histone deacetylases, effective on mammalian cells as well as on intracellular apicomplexan parasites, such as Toxoplasma gondii, in the tachyzoite and bradyzoite stages. This molecule is characterized by two parts: the zinc-binding group, responsible for the binding to the histone deacetylase, and the cyclic tetrapeptide moiety, which plays a crucial role in cell permeability. Recently, we have shown that the cyclic tetrapeptide coupled with a fluorescent diethyl-amino-coumarin was able to maintain properties of cellular penetration on human cells. Here, we show that this property can be extended to the crossing of the Toxoplasma gondii cystic cell wall and the cell membrane of the parasite in its bradyzoite form, while maintaining a high efficacy as a histone deacetylase inhibitor. The investigation by molecular modeling allows a better understanding of the penetration mechanism.